P15 Multiple defects of the immunoregulatory system contribute to the development of autoimmune hepatitis. (6th September 2011) - Wang, P; Longhi, M S; Mieli-Vergani, G; Vergani, D; Ma, Y
Abstract : Introduction: Concordance for autoimmune hepatitis (AIH) is rare within families, though non-hepatic autoimmune disorders are frequent among first degree relatives (FDR) of AIH patients. While a defect in immunoregulation has been demonstrated in AIH patients, the mechanism preventing the development of AIH in FDR, who share genetic background, remains to be elucidated. Aim: To investigate multiple immunoregulatory systems in AIH patients and their FDR. Method: 44 children with AIH (33 AIH-1 and 11 AIH-2, median age 13.5 yrs, 23 females), 65 FDR from 34 families [23 fathers, 47 yrs (38–58); 28 mothers, 44 yrs (24–53) and 14 siblings, 7 females, 13 yrs (5–24)] and 42 healthy subjects [HS, 36 yrs (22–54), 37 females] were studied. Frequency of conventional CD4 pos CD25 pos regulatory T-cells (Tregs), CD4 pos CD25 high CD127 neg True Tregs, CD4 pos PD-1 pos and CD8 pos CD28 neg T cells, CD3 neg CD56 pos natural killer (NK) cells, CD3 pos TCRVa24 pos /TCRVb11 pos invariant NKT cells (iNKT) was defined by flowcytometry. Tregs and CD4 pos PD-1 pos T cells were purified from PBMCs using immunomagnetic beads. CD25 neg and PD-1 neg cells (responders) were co-cultured for 5 days with cells with regulatory potential and their proliferation was measured by 3 H-thymidine incorporation. Results: Conventional Tregs were lower in patients (10.5%±1.1) than FDR (15.9%±1.1, p=0.001) and HS (14.7%±1.7, p=0.04), while 'True' Tregs were similar in all (6.0%±0.6, 6.3%±0.4 and 6.2%±0.5). CD4 pos PD-1 pos T cells were lower in patients (1.7%±0.2) and in FDR (1.9%±0.2) than in HS (3.0%±0.2, p<0.0001 for patients and p=0.0007 for FDR). NK cells were lower in patients (8.6%±1.2) than in FDR (15.8%±1.2, p=0.0004) and HS (12.3%±0.9, p=0.02). CD8 pos CD28 neg T cells in patients tended to be lower (8.8%±1.46) than in FDR (12.43%±1.56, p=0.18) and HS (13.1%±1.82, p=0.11). The frequency of iNKT cells was similar in all groups. 'True' Tregs decreased CD25 neg cell proliferation by 13.6% in patients, 28.8% (p=0.007) in FDR and 36.9% (p<0.0001) in HS, while CD4 pos PD-1 pos T cells decreased similarly PD-1 neg cell proliferation in patients (25.4%), FDR (22.5%) and HS (26.8%). Conclusion: A numerical impairment of CD4 pos PD-1 pos T cells in patients and their FDR suggests that these defects are genetically determined and account for family clustering of autoimmune disorders. A numerical impairment of conventional Tregs and functional impairment of CD4 pos CD25 high CD127 neg 'True' Tregs, confined to patients with AIH, may be crucial to loss of liver tolerance.